MOBILE PHONE RECOMMENDER USING MULTI CRITERIA DECISION MAKING ALGORITHM - J, Ragaventhiran; M, Sindhuja; N, Prasath; B, Muthu Kumar; M, Islabudeen (Malaysian Journal of Computer Science, 2022)
A study found that the depression rate is growing at an alarming rate among everyone. Many people who report symptoms of depression mostly have not been diagnosed or underwent treatments for it. If they do not get proper treatments like medication, therapy, guidance or counselling, it would be difficult for them to lead a happy and stress-free lifestyle. India is already on the cusp of a health crisis, and we urgently require a long-term solution to the problem of depression. People are more inclined to open it up to a smart machine than to a human, according to a recent study. Digital interfaces are gaining traction as feasible options for closing the gap and making mental diagnosis and treatment more accessible and inexpensive to everybody. The aim of the project is to develop a chatbot called Therapy Bot using sentiment analysis and cognitive behavioral therapy to predict the mental health status of an individual. Moreover, the chatbot can serve as a good companion to the affected by communicating with friendly manner and help them recover. The chatbot will personalize its responses based on the user's answer to keep the conversation interesting. The chatbots can be used as a complement to treatment or as a kind of interim support while waiting for an appointment. The benefit of such a method is that, rather than reaching a point where a trip to a psychologist is required, an online free version will reach a large number of people, mitigate the negative effects of depression, and contribute to a better of society.